TOXICOLOGICAL SCREENING FOR POLYHERBAL COMBINATIONS OF MORINGA OLEIFERA AND EMBELIA RIBES IN EXPERIMENTAL ANIMALS. - Srivastava, Richa; Srivastava, Sajal; Singh, Satya Prakash (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present study, aqueous ethanolic extract of Moringa oleifera and Embelia ribes was evaluated for the acute and subacute toxicity in combination. Despite the wide use of in folk medicine, no study has been published in the scientific literature about their in combination toxicological profile. In the acute toxicity test, oral administration of 2 g/kg of combination produced neither mortality nor changes in behavior or any other physiological activities in mice. Methods: The animals were observed for toxic symptoms continuously for the first 4 h after dosing. Finally, the number of survivors was noted after 24 h, and these animals were then maintained for a further 13 days with observations made daily. Result: In subacute toxicity studies, no mortality was observed when the two doses of 1 or 2 g/kg day of 50% aqueous ethanolic extract in combination were administered for 28 days in mice. Hematological analysis showed no marked differences in any of the parameters examined in either the control or treated group of both sexes. The urinalysis was negative for glucose, ketogenic bodies, casts, red blood cells, and albumin in the control and treatment groups. There were no significant differences in the body and organ weights between control and treated animals of both sexes. Conclusion: The combination was found safe in acute and subacute toxicities while chronic toxicity studies are further required for the support of the safe and sound use of this traditional plants.